A Review of SCUBA Diving Impacts and Implication for Coral Reefs Conservation and Tourism Management - Zainal Abidin, Siti Zulaiha; Mohamed, Badaruddin (EDP Sciences, 2014)
Dive tourism has become important in term of magnitude and significantly contributes to regional economies. Nevertheless, in the absence of proper controls and enforcement, unplanned tourism growth has caused environmental degradation which undermines the long-term sustainability of the tourism industry. The purpose of this paper is to explore factors that contribute to the SCUBA diving impacts on coral and fish communities. This paper explains the causes of a certain event, validating the problem of impacts, defining the core issues and identifies possible causes leading to an effect. The phenomenon of diving impacts on coral reefs is a result of intensive use of dive site over the long-term. The divers can reduce their impacts towards coral reefs through responsible diving behaviors. The causes of cumulative diver’s contacts are more complicated than it seems. In response, this paper proposes the best mitigation strategies that need to be considered for future dive tourism management.